Influence Of Leadership Style And Orientation Of Work On Employee Performance in Government Tanggamus District - Agus Behaki (Dinar Islamic Review, 2021)
The quality of human resources becomes the main thing in the employment system in a government or private organization. Demands from the community for better services forced various relevant government agencies to continue to reform by improving the performance of their employees. Regarding this problem, researchers are interested in further studying the performance of employees at the Tanggamus Regency Government Secretariat office in providing services to the community and employee performance. This research is field research with quantitative methods, data collection using a questionnaire with 49 respondents and using multiple linear regression tests. The result showed that simultaneously Leadership Style and Work Orientation significantly positively affect employee performance.